Vietnamese pharmacogenomic variation in global context: a systematic review and meta-analysis for clinical implementation - Van Thi Bich Hoang; Anh Van Tran; Tham Thi Bui; Quynh Thi Vu; Mai Thi Quynh Ngo; Khai Van Nguyen; Phuong Thi Thu Nguyen (Frontiers in Pharmacology, 2026)
Background Population-frequency evidence is indispensable for planning pharmacogenomic services, but broad ancestry categories do not reliably capture the distribution of clinically important alleles, haplotypes, and structural variants. We undertook a systematic synthesis of pharmacogenetic variation reported in Vietnamese populations and evaluated its relevance to clinical implementation. Methods Following a prospectively registered protocol and PRISMA 2020, we searched international and Vietnamese sources through 30 December 2025. Reports were eligible when they described Vietnamese participants and provided, or materially informed, pharmacogenetic genotype or allele-frequency evidence. Variant representations were reconciled across rsIDs, star alleles, haplotypes, copy-number changes, hybrid alleles, repeats, and HLA alleles. For variants with at least two independent rows, frequencies were synthesized with random-effects logit models; single-row estimates used Wilson confidence intervals. Orientation-validated single-rsID variants were compared with the 1,000 Genomes AFR, AMR, EAS, EUR, and SAS superpopulations with false-discovery-rate control. Results Of 207 records, 54 full-text reports were assessed and 52 were retained in the systematic review; 46 independent reports or datasets contributed to the primary meta-analysis. The evidence comprised 108 analysis-ready variant representations across 25 pharmacogenes, including 66 single-rsID and 42 complex or non-rsID representations. Ninety-five representations were supported by one study row. Among included reports, 11 were at low, 38 at moderate, and 3 at high risk of bias; none of the 46 quantitative reports was classified as high risk. Prominent estimates were VKORC1 -1639G>A, 89.91% (95% CI 81.13-94.86); VKORC1 1173C>T, 85.43% (81.61-88.56); SLCO1B1 c.388A>G, 75.95% (69.75-81.22); CYP3A5 *3, 60.81% (44.96-74.67); ABCB1 3435C>T, 40.28% (32.62-48.44); ABCG2 c.421C>A, 36.00% (29.67-42.86); CYP2C19 *2, 27.90% (26.57-29.27); NAT2 *6, 27.00% (18.69-37.31); and CYP2C19 *3, 5.74% (4.82-6.82). Eighteen of 20 variants in the principal global comparison were within 5 percentage points of EAS; larger differences occurred for ABCB1 3435C>T (−19.9 points) and CYP3A5 *3 (−7.2 points). Conclusion Vietnamese pharmacogenomic frequencies are regionally East Asian-adjacent but not interchangeable with a generic East Asian reference. Implementation should combine local frequency evidence with guideline strength, preventable clinical harm, medication use, and assay complexity, while preserving haplotype and structural-variant information. Systematic Review Registration https://doi.org/10.17605/OSF.IO/7VTNW , identifier 7VTNW.